2022
DOI: 10.1186/s11689-022-09436-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological changes in FMR1 premutation carriers and onset of fragile X-associated tremor/ataxia syndrome

Abstract: Background Carriers of the FMR1 premutation are at increased risk of developing a late-onset progressive neurodegenerative disease, fragile X-associated tremor/ataxia syndrome (FXTAS), characterized by intention tremor, gait ataxia, and cognitive decline. Cross-sectional studies to date have provided evidence that neuropsychological changes, such as executive function alterations, or subtle motor changes, may precede the onset of formal FXTAS, perhaps characterizing a prodromal state. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
(57 reference statements)
2
12
0
Order By: Relevance
“…The present findings are consistent with previous studies on male premutation carriers [ 10 , 29 , 62 ]. For example, an accelerated decline in executive functions, including visual working memory and inhibitory control, was found in a group of male premutation carriers compared to the control group [ 10 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The present findings are consistent with previous studies on male premutation carriers [ 10 , 29 , 62 ]. For example, an accelerated decline in executive functions, including visual working memory and inhibitory control, was found in a group of male premutation carriers compared to the control group [ 10 ].…”
Section: Discussionsupporting
confidence: 94%
“…The Fragile X Syndrome (FXS) is the most common cause of intellectual disability and autism as well as additional difficulties. It is caused by the absence of the FMR1 protein [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. The syndrome is caused by more than 200 repeats of a sequence of three nucleotides, Cytosine–Guanine–Guanine (CGG), located in the promoter region on the long arm of the X chromosome [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that children with premutations mostly have conventional developmental profiles and trajectories, minor but significant delays in fine motor abilities have been reported at 18 months of age (Wheeler et al, 2021). A longitudinal study of 64 male premutation carriers of Fmr1 without FXTAS reported decreased executive function and subtle motor changes (Famula et al, 2022). Additionally, pre-FXS mutations are associated with various clinical characteristics, including early ovarian failure and a high prevalence of hypertension, thyroid illness, fibromyalgia, peripheral neuropathy, and seizures (Rodriguez-Revenga et al, 2009).…”
Section: Clinical Datamentioning
confidence: 99%